Minding Quanta and Cosmology - Pribram, Karl H. (Zygon, 2009)
Abstract. The revolution in science inaugurated by quantum physics has made us aware of the role of observation in the construction of data. Eugene Wigner remarked that in quantum physics we no longer have observables (invariants), only observations. Tongue in cheek, I asked him whether that meant that quantum physics is really psychology, expecting a gruff reply to my sassiness. Instead, Wigner beamed understanding and replied “Yes, yes, that's exactly correct.” David Bohm pointed out that were we to look at the cosmos without the lenses of our telescopes we would see a hologram. I extend Bohm's insight to the lens in the optics of the eye. The receptor processes of the ear and skin work in a similar fashion. Without these lenses and lenslike operations all of our perceptions would be entangled as in a hologram. Furthermore, the retina absorbs quanta of radiation so that quantum physics uses the very perceptions that become formed by it. In turn, higher-order brain systems send signals to the sensory receptors so that what we perceive is often as much a result of earlier rather than just immediate experience. This influence from inside out becomes especially relevant to our interpretation of how we experience the contents and bounds of cosmology that come to us by way of radiation.